The Iraw Tengkayu Culture: Stability of Behaviour in Solidarity Among Tribes in Tarakan City - Handy Wiranto; Jefri Setyawan (Nusantara Journal of Behavioral and Social Science, 2025)
Iraw Tengkayu is a cultural tradition preserved by the people of Tarakan City, North Kalimantan, that engages various ethnic groups in a shared ceremonial event. This tradition not only symbolizes cultural continuity but also serves as a psychosocial platform to foster interethnic solidarity and cultural resilience in a multicultural society. This study aims to examine the psychosocial processes embedded in the Iraw Tengkayu celebration, focusing on social connectedness, collective identity formation, intrinsic motivation, environmental consciousness, and the symbolic meanings constructed within the community. Employing a qualitative realist approach, data were collected through semi-structure interviews with four key informant organizers and local participants. Thematic analysis was employed to identify recurring patterns, with triangulation used to enhance the validity of the findings. The findings demonstrate that Iraw Tengkayu strengthens social cohesion through interethnic rituals, reinforces inclusive cultural identity, and promotes civic participation. The celebration also nurtures ecological awareness and sustains a collective memory rooted in gratitude and togetherness. Theoretically, this study contributes to understanding how cultural rituals function as psychosocial mechanisms for identity integration and solidarity in diverse settings. Practically, it emphasizes the importance of integrating cultural heritage into public policy to foster inclusive citizenship, social harmony, and environmental responsibility in multicultural contexts.